Effectiveness of home pharmaceutical interventions in metabolic syndrome: a randomized controlled trial - Maria da Glória Batista de Azevedo; Roseana Souza Pedrosa; Caroline Mapurunga Aoqui; Rand Randall Martins; Toshiyuki Nagashima Junior (Universidade de São Paulo, 2017)
ABSTRACT Metabolic syndrome (MetS) is a group of different risk factors that raises the chances of develop several health problems such, as cardiovascular disease and diabetes. There are few cases in literature of studies that specifically address the use of pharmaceutical care in MetS. The aim of study was to evaluate the effectiveness of home pharmaceutical interventions in patients with this syndrome. The randomized clinical trial was conducted in subjects with diagnosis of MetS treated in a basic unit of health from Cuité, Paraíba. The patients were randomized in a 1:1 ratio to two groups: intervention (IG) and control (CG). The IG received monthly individual pharmaceutical interventions, while the CG did not. The effectiveness of the intervention protocol was measured after six months, comparing the hemodynamic values, anthropometric, biochemistry, cardiovascular risk, medication adherence, drug related problems (DRP) and quality of life. The sample consisted of 63 individuals (33 IG and 30 CG) and older than 60 years. The majority of pharmaceutical interventions were educational and/or behavioral. In the intervention group, significant differences were observed in the parameters systolic and diastolic blood pressure, triglycerides, medication adherence and DRP. The pharmaceutical interventions at home were effective in improving medication adherence, decreasing DRPs and helping to control components of the metabolic syndrome.